Green supply chain management in Latin America: Systematic literature review and future directions - Teixeira, Adriano Alves; Moraes, Tiago Estrela da Cunha; Stefanelli, Nelson Oliveira; de Oliveira, Jorge Henrique Caldeira; Teixeira, Talita Borges [UNESP]; de Souza Freitas, Wesley Ricardo (My University, 2020)
The implementation and scope of green supply chain management (GSCM) practices vary among organizations. In emerging economies, new production chain models are required, but little is known about GSCM in these countries, especially in Latin America. Thus, this paper aims to highlight the state-of-the-art of GSCM in Latin America, through a systematic review of the literature (using Scopus and Web of Science databases) and suggests a research agenda with nine recommendations. Results show underexplored themes, such as GSCM benefits, GSCM and key performance indicators, and GSCM and competitive advantage. This study is the only systematic review of GSCM in Latin America, providing a useful research agenda for academics, managers, and policymakers. For instance, this paper contributes to the advancement of the UN Sustainable Development Goals (SDG) in Latin America by suggesting that scholars, practitioners, and governments shed lights on sustainable production and consumption standards (SDG 12), measures to combat climate change and its impact (SDG 13), and the best means of implementation and global partnerships for sustainable development (SDG 17).
Keywords: circular economy; environmental management; environmental sustainability; green human resource management; literature review; supply chain; sustainability